ТОНКИЙ ЕЛЕКТРОМАГНІТНИЙ ЕКРАН КОМПОЗИЦІЙНОЇ СТРУКТУРИ, ВИКОНАНИЙ НА ОСНОВІ МАГНІТНОЇ РІДИНИ - Глива, В.А.; Подольцев, О.Д.; Болібрух, Б.В.; Радіонов, О.В. (Інститут електродинаміки НАН України, Київ, 2022)
A thin electromagnetic shield (0.25 − 0.50 mm thick) were developed, which has a composite structure and was made on a magnetic fluid deposited on a dielectric substrate. Experimental researches of its shielding and electromagnetic properties were carried out. It is shown that the screening coefficient of a low-frequency magnetic field for such a screen is 2.4 − 7.8. The screening coefficient for an ultrahigh-frequency magnetic field is 3.0 − 9.3. The values of these coefficients depend on the thickness of the screen. The calculation-experimental method is proposed for the determine of the effective magnetic permeability of the composite screen material. This method is using the well-known analytical solution of the magnetostatic problem for a thin spherical shell and the results of measuring screening coefficients for a screen of spherical (or nearly spherical) shape. The obtained relative values of the magnetic permeability of the material for the case of a low-frequency magnetic field are 420 − 1050. These values depend little on the thickness of the screen. References 10, table 2, figures 2.